KESESUAIAN AIR SUNGAI KAMPAR UNTUK BUDIDAYA IKAN PATIN SISTEM KERAMBA DI DESA KUALA PANDUK KECAMATAN TELUK MERANTIKABUPATEN PELALAWAN - FIRDAUS, FIRDAUS; Edial, MT., Drs. Helfia; Farida, Farida (Pendidikan Geografi, 2014)
ABSTRACKThe river conservation is one the steps to solve the fish population. Although it was not revealed the significant result, however the steps was a multipurpose business, due to the anticipation of the fish population on the river was continuing restricted, also as media to maintain the various river organism in Indonesia. This step was as the way to improve Indonesian nutrients. For that reason, the river sources conservation of Pangius, sp on the river of Kampar, of course to be expected the population of the fish was possible to protect. This research aims to find out data, informations and discussion about the quality of the water of Kampar River was suitable to sanctuary system for Pangius, sp at the village Kuala Panduk of Teluk Meranti District in Pelalawan Regency. It consisted of physical and chemical condition analysis. The type of this research was descriptive study. The determination of sample in this research used sampling area technique (regional sample) taking randomly on the river of Kampar at the village Kuala Panduk. The result of research showed that: the quality of water of Kampar River at the village Kuala Panduk of Teluk Meranti District in Pelalawan Regency from physical parameter (temperature, turbidity, and debit) temperature on the sample 1 and 3 have fulfilled the required conditions, but for sample 2 did not have. To the turbidity for sample 1, 2 and 3 did not have fulfilled the required conditions. And to debit of water for sample 1, 2 and 3 have fulfilled the required conditions to the river sources conservation of Pangius, sp by using sanctuary system. While for the chemical parameter (pH, DO, CO2, NH3 and H2S). pH for the sample 1,2 and 3 have fulfilled the required conditions, DO for the sample 1 did not have, while to sample 2 and 3 have fulfilled the required conditions. To CO2 for the sample 1, 2 and 3 have fulfilled the required conditions. For NH3 and H2S at the sample 1, 2 and 3 did not have fulfilled the required conditions to the river sources conservation of Pangius, sp by using sanctuary system.